Qualidade da educação: relações entre características de contexto e os resultados das avaliações em larga escala nos municípios de pequeno porte da região sul do Brasil - Soligo, Valdecir (Universidade do Vale do Rio dos Sinos, 2013)
In recent decades, Brazil has undergone important transformations in its social and economic aspects. This does not mean, however, that issues such as social inequality, regional inequality, quality of education, income distribution, poverty, poverty, among others, have been overcome. Rather, they are the focus of concern of scholars and researchers from different fields of knowledge. The social, cultural and economic inequality of Brazilian municipalities point to the need to consider the regional space as central to deepening our knowledge of reality. The aim of this study was to analyze the relationship between IDEB and features of context, measured by the Gini Index indicators, Incidence of Poverty, Income and per capita monthly family illiteracy rate for the population aged 15 years or older. The survey was conducted in databases MEC / INEP and IBGE, from survey data about 327 small towns in southern Brazil, which have IDEB for the years 2005, 2007 and 2009. As a result, it was revealed the existence of a relationship between the average IDEB and social indicators. The values pointed to greater consistency of relationships between variables for municipalities than for State or Region South The composition of population statistics pointed to a methodological problem Proof of Brazil. This does not assess all the small towns and therefore many do not have the cycles to IDEB 2005, 2007 or 2009, which influences the composition of the Index for the States and for the region. Another fact revealed by the analysis concerns the fragility of statistics generalist, which ignores the differences between the municipalities, using data for states or large regions, homogenising social characteristics, through indicators and indices.
Keywords: IDEB; Indicadores sociais; Municípios de pequeno porte; Social indicators; Small municipalities; ACCNPQ::Ciências Humanas::Educação